Effect of immobilization of the distal interphalangeal joint of fingers on grip strength. (June 2018) - Wu, Feiran; Mehta, Saurabh Sagar; Dickson, David; Catchpole, Dee; Ng, Chye Yew
Arthrodesis of the distal interphalangeal joint of the finger is an effective salvage treatment for end-stage arthropathy of the joint. This study aimed to evaluate the effect of simulated fusion of individual distal interphalangeal joints on the overall grip strength of the hand. Custom moulded thermoplastic splints were used to simulate fusion by immobilizing the index, middle, ring and little fingers' distal interphalangeal joints in turn in both hands of 56 healthy participants. Testing was performed with no immobilization and after immobilization of each of the individual digits. Grip strengths reduced significantly following immobilization of the distal interphalangeal joint. The degree of reduction became progressively more pronounced from the index to the little fingers (12%, 18%, 24% and 25%, respectively) and was similar for the dominant and non-dominant hands. This information may have clinical application when counselling patients regarding fusion of the distal interphalangeal joint of the fingers.